1998
DOI: 10.1093/carcin/19.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of chemopreventive synergism between (-)-epigallocatechin- 3-gallate and curcumin in normal, premalignant and malignant human oral epithelial cells

Abstract: An in vitro model for oral cancer was used to examine the growth inhibitory effects of chemopreventive agents when used singly and in combination. The model consists of primary cultures of normal oral epithelial cells, newly established cell lines derived from dysplastic leukoplakia and squamous cell carcinoma. Two naturally occurring substances, (-)-epigallocatechin-3-gallate (EGCG) from green tea and curcumin from the spice turmeric were tested. Cells were treated singly and in combination and effects on gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(118 citation statements)
references
References 35 publications
3
115
0
Order By: Relevance
“…A key question is whether these agents have opposing actions with respect to other keratinocyte end points. As noted above, treatment of normal human oral epithelial cells with EGCG or curcumin results in a reduction in cell number (64). Our study indicates that both EGCG and curcumin reduce normal human keratinocyte cell number (not shown).…”
Section: Figsupporting
confidence: 77%
“…A key question is whether these agents have opposing actions with respect to other keratinocyte end points. As noted above, treatment of normal human oral epithelial cells with EGCG or curcumin results in a reduction in cell number (64). Our study indicates that both EGCG and curcumin reduce normal human keratinocyte cell number (not shown).…”
Section: Figsupporting
confidence: 77%
“…It also suppresses the proliferation of a number of transformed cell types in vitro, including breast (Simon et al, 1998;Ramachandran and You, 1999), colon (Chen et al, 1999) and oral epithelial cells (Khafif et al, 1998). The anti-proliferative effects of curcumin include blocks at specific cell cycle stages, particularly a G2/M block (Hanif et al, 1997;Mehta et al, 1997;Ramachandran and You, 1999;Holy, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Agullo et al (1994) have demonstrated that quercetin has potent cytotoxicity against colon cancer cells in vitro, and that this is associated with antiproliferative activity. Literature data (Khafif et al, 1998) show a synergistic chemopreventive effect between EGCG and curcumin on the cell cycle of premalignant and malignant human oral epithelial cells. Flow cytometric studies have showed that EGCG and curcumin inhibited growth by different mechanisms; EGCG blocked all cells in the G 1 phase, whereas curcumin blocked cells in S/G 2 M phases.…”
Section: Discussionmentioning
confidence: 99%